Interannual Climate Variability Impacts on Rainfall Extremes and Flooding - Panggabean, Jogi Ruben Natanael; Syamsudin, Fadli; Suaydhi, Suaydhi; Purba, Noir; Feng, Xingru (Universitas Diponegoro, 2026)
The Bandung metropolitan region has faced escalating flood threats (2014–2024); however, oceanic climate–rainfall relationships remain uninvestigated. This study investigates the interannual climate variability influencing extreme precipitation and flooding using historical records and the GPM-IMERG satellite measurements, which had a 90.4% correlation with BMKG. Bojongsoang (117 events), Lembang (49 events), and Braga (42 events) emerge as highest-risk areas. The peak flooding in January 2020 (15 events) coincided with the La Niña and negative Indian Ocean Dipole (IOD) phases. The average daily maximum rainfall during the wet season was 62 mm, compared with 41 mm in the dry season, with 36 heavy rain days versus 8 days. La Niña increased heavy rain days to 62.5 days compared with El Niño (38.6 days) and extreme rainfall to 399.6 mm versus 244.2 mm. Negative IOD enhanced the daily maximum to 76.8 mm versus 56.8 mm during the positive phases. Flood months showed 81.3 heavy rain days versus 14.4 in normal months. Early warning thresholds were established at >70 mm daily maximum, >60 heavy rain days, and >400 mm extreme precipitation.